Beginning CSS3 - Powers, David; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Beginning CSS3 teaches you how to style web pages using Cascading Style Sheets (CSS)$1 (Bthe language of web design. Starting from first principles, you$1 (Bll learn through a series of practical exercises how to change the default look of HTML tags, adding color, backgrounds, and borders. The book demystifies core concepts, such as the CSS box model and selectors, giving you the confidence and knowledge to create innovative and flexible page layouts. You$1 (Bll also learn how to create rounded corners, drop shadows, and gradients without the need for images, using the latest CSS3 techniques.s
Keywords: Computer science; Computer Science; Computer Science, general